THIRD WAVE COFFEE DAN STRATEGI GASTRODIPLOMASI INDONESIA DI PASAR AMERIKA SERIKAT PADA TAHUN 2016-2019 - Ahda Savira Diandra, (2022)
The Thirdwave Coffee phenomenon that occurred in the United States became an opportunity for Indonesia. This is because the United States has been the largest coffee importer in Indonesia since 2000. Even though in its implementation, Indonesia faces various obstacles and challenges. In responding to these obstacles and challenges, the government has made various efforts to take advantage of various opportunities that Indonesia has, such as implementing a gastrodiplomacy strategy using coffee. To be able to develop the analysis in this research, the theory of public diplomacy and the concept of gastrodiplomacy are used. This research uses qualitative method with descriptive analysis research type. The final result of this study reveals that the implementation of the gastrodiplomacy strategy using coffee in the United States market in 2016-2019 has been carried out using various elements of gastrodiplomacy and involving various actors, both state and non-state actors